2005
DOI: 10.1507/endocrj.52.455
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Percutaneous Ethanol Injection Therapy in Benign Nodular and Cystic Thyroid Diseases: Long-term Follow-up Experience

Abstract: Abstract. This study was designed to clarify the long-term efficacy and safety of percutaneous ethanol injection (PEI) therapy in benign nodular and cystic thyroid diseases, and to evaluate response by criteria defined as disappearance of hot nodule. Solid nodule and complex cyst were classified into three groups in accordance with volume reduction. In autonomously functioning thyroid nodule (AFTN), disappearance of hot nodule with normalization of thyroid hormone level and restored extra-nodular uptake was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
0
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 34 publications
2
75
0
7
Order By: Relevance
“…This suggests that the ethanol is continuously absorbed by the solid part of the nodule, resulting in a progressive volume reduction. Another study (11) evaluating the decrease in nodular size with time showed that the reduction at long term is similar in different types of nodules, confirming that solid nod ules do not respond as fast as cystic ones to the scleros ing effect of the ethanol.…”
Section: Discussionmentioning
confidence: 86%
“…This suggests that the ethanol is continuously absorbed by the solid part of the nodule, resulting in a progressive volume reduction. Another study (11) evaluating the decrease in nodular size with time showed that the reduction at long term is similar in different types of nodules, confirming that solid nod ules do not respond as fast as cystic ones to the scleros ing effect of the ethanol.…”
Section: Discussionmentioning
confidence: 86%
“…Occasionally, temporary vocal fold paralysis and dysphonia or, rarely, transient thyrotoxicosis may occur 22 . In the largest set of 432 complex cysts, Lee and Ahn reported transient localized pain in 32 (7.9%) and temporary vocal fold paralysis in only 3 (0.7%) patients 10 . Apart from short-term localized pain, no other complications were noted in our study.…”
Section: Discussionmentioning
confidence: 97%
“…During regular check-ups, the decrease in cyst volume was measured using the volume reduction rate (VRR) calculated as follows: initial cyst volume -final cyst volume / initial cyst volume × 100 = result % (ref. 10 ). The VRR was calculated at 1, 3 and 6 months after the last PEI.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10][11][12] While most previous studies focused on thyroid cysts, only a few cases of TGDC have been reported. 13,14 Our thyroid team has applied EA to thyroid cysts and TGDC for several years.…”
mentioning
confidence: 99%